2011
DOI: 10.1371/journal.pone.0028340
|View full text |Cite
|
Sign up to set email alerts
|

Mitragynine Attenuates Withdrawal Syndrome in Morphine-Withdrawn Zebrafish

Abstract: A major obstacle in treating drug addiction is the severity of opiate withdrawal syndrome, which can lead to unwanted relapse. Mitragynine is the major alkaloid compound found in leaves of Mitragyna speciosa, a plant widely used by opiate addicts to mitigate the harshness of drug withdrawal. A series of experiments was conducted to investigate the effect of mitragynine on anxiety behavior, cortisol level and expression of stress pathway related genes in zebrafish undergoing morphine withdrawal phase. Adult zeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 53 publications
3
41
0
Order By: Relevance
“…However, Khor et al () reported on the neuroprotective effects of caffeine against anxiety in adult male zebrafish that had been exposed to dexamethasone as an early‐life stressor, suggesting that the timing of drug administration is a critical factor in determining stress‐related outcomes. Additional research has also indicated that zebrafish can be used to model withdrawal symptoms, as discontinuation of ethanol, diazepam, cocaine, and morphine produces anxiogenic‐like behaviors (e.g., increased erratic movements, number and duration of freezing bouts, latency to enter the top tank region, and bottom dwelling) and endocrine responses measured by increased levels of whole‐body cortisol (Lopez‐Patino et al, ; Cachat et al, ; Khor et al, ; Mathur and Guo, ). Overall, these pharmacological data suggest comparable molecular mechanisms of control for stress‐related behaviors between zebrafish and humans and, thus, demonstrate the high predictive validity of zebrafish models to screen for psychoactive drugs.…”
Section: Behavioral Testing In Zebrafish and Its Implications For Depmentioning
confidence: 99%
“…However, Khor et al () reported on the neuroprotective effects of caffeine against anxiety in adult male zebrafish that had been exposed to dexamethasone as an early‐life stressor, suggesting that the timing of drug administration is a critical factor in determining stress‐related outcomes. Additional research has also indicated that zebrafish can be used to model withdrawal symptoms, as discontinuation of ethanol, diazepam, cocaine, and morphine produces anxiogenic‐like behaviors (e.g., increased erratic movements, number and duration of freezing bouts, latency to enter the top tank region, and bottom dwelling) and endocrine responses measured by increased levels of whole‐body cortisol (Lopez‐Patino et al, ; Cachat et al, ; Khor et al, ; Mathur and Guo, ). Overall, these pharmacological data suggest comparable molecular mechanisms of control for stress‐related behaviors between zebrafish and humans and, thus, demonstrate the high predictive validity of zebrafish models to screen for psychoactive drugs.…”
Section: Behavioral Testing In Zebrafish and Its Implications For Depmentioning
confidence: 99%
“…Psychophysiological compounds including diazepam, serotonin, a selective serotonin reuptake inhibitor Fluoxetin, a central-type benzodiazepine receptor inverse agonist FG-7142, and an N-methyl-d-aspartate receptor antagonist MK-801 also modify locomotor activity (Kang et al, 2010; Matsuda et al, 2011b, 2013b; Winder et al, 2012). Recent reports have indicated that the swimming pattern of a fish in a tank can be used to evaluate psychomotor activity (Faganello and Mattioli, 2007; Cachat et al, 2010; Grossman et al, 2010; Maximino et al, 2010a,b; Khor et al, 2011, 2013; Matsuda et al, 2011a; Piato et al, 2011). The scototaxis test (light/dark preference test) has been developed, and used for measuring psychomotor activity (Faganello and Mattioli, 2007; Blaser and Rosemberg, 2012).…”
Section: Psychophysiological Effect Of Crh In Fishmentioning
confidence: 99%
“…Automated methods have recently been developed in these species to track the position of individuals alone or in a group (Branson et al, 2009; Swierczek et al, 2011) and to categorize behavior (Dankert et al, 2009; Kabra et al, 2013). The zebrafish has emerged as an important vertebrate model organism for developmental biology, neurobiology, and human disease models, and is now used as a genetic model organism for the study of the mechanisms modulating complex behaviors in vertebrates such as depression and anxiety (Blaser et al, 2010; Lee et al, 2010; Cachat et al, 2011; Vermoesen et al, 2011; Zakhary et al, 2011; Ziv et al, 2013), sleep (Zhdanova et al, 2001; Appelbaum et al, 2009), or addiction (Petzold et al, 2009; Khor et al, 2011). The permeability, small size, genetic tractability, transparency, and low cost of zebrafish make them highly suitable for large-scale genetic and chemical screens (Driever et al, 1996; Granato et al, 1996; Haffter and Nusslein-Volhard, 1996).…”
mentioning
confidence: 99%